1999
DOI: 10.1152/jappl.1999.86.4.1116
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of absorption atelectasis during anesthesia: a mathematical model

Abstract: Recent computed tomography studies show that inspired gas composition affects the development of anesthesia-related atelectasis. This suggests that gas absorption plays an important role in the genesis of the atelectasis. A mathematical model was developed that combined models of gas exchange from an ideal lung compartment, peripheral gas exchange, and gas uptake from a closed collapsible cavity. It was assumed that, initially, the lung functioned as an ideal lung compartment but that, with induction of anesth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
11

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(72 citation statements)
references
References 28 publications
2
59
0
11
Order By: Relevance
“…Poorly ventilated lung units-such as those that are the cause of periodic breathing-are likely to collapse due to atelectasis, especially for high oxygen concentrations. 11,12 By allowing compartment volume to vary, and therefore to be dependent on the ventilation of the lung, the effect that lung volume has on periodic breathing can be investigated. Subsequently, whether there is a link to the prevention, or delay, of total lung collapse may be determined.…”
Section: Incorporating Variable Compartment Volume Into the Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…Poorly ventilated lung units-such as those that are the cause of periodic breathing-are likely to collapse due to atelectasis, especially for high oxygen concentrations. 11,12 By allowing compartment volume to vary, and therefore to be dependent on the ventilation of the lung, the effect that lung volume has on periodic breathing can be investigated. Subsequently, whether there is a link to the prevention, or delay, of total lung collapse may be determined.…”
Section: Incorporating Variable Compartment Volume Into the Modelmentioning
confidence: 99%
“…The percentage of inspired oxygen is increased to F I = 0.8, in agreement with experimental observation that the incidence of pulmonary collapse is greater with higher levels of inspired oxygen, even in the absence of restrictions in ventilation. 11,12 Indeed, it has been observed that atelectasis can result from high levels of inspired oxygen. 13 It should be noted that the parameters used to produce these solutions do not lead toward total lung collapse.…”
Section: Summary Of Computationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Joyce e Williams postularam que após a indução anestésica as vias aéreas das regiões pulmonares dependentes se fecham e essas áreas se comportam como uma cavidade fechada passível de colapso. Utilizando um modelo matemático, esses autores propuseram que a oxigenação prévia e o uso de altas frações inspiradas de oxigênio aumentam a captação de gás das áreas pouco ventiladas do pulmão e eram os principais responsáveis pela formação de atelectasias 34 . Rothen e col. observaram em 12 pacientes submetidos à intervenção cirúrgica eletiva sob anestesia geral, que quando FiO 2 de 1 era utilizada após manobra de expansão pulmonar até a capacidade vital (pressão de 40 cmH 2 O nas vias aéreas), atelectasias eram observadas em tomografias de tórax obtidas em até cinco minutos.…”
Section: Mecanismos Do Colapso Pulmonar Intra-operatóriounclassified